Radiosynthesis and preclinical evaluation of [18F]FEM as a potential novel PET probe for tumor imaging. Issue 12 (15th June 2020) - Jiang, Yanping; Zhou, Wenlan; Hu, Kongzhen; Han, Yanjiang; Sun, Penghui; Wang, Quanshi; Li, Guiping; Wu, Hubing; Tang, Ganghua; Huang, Shun
Graphical abstract: Highlights: Synthesis of [ 18 F]FEM as a potential novel PET probe for tumor imaging. [ 18 F]FEM can specifically accumulate at the tumor site of five different tumor models. [ 18 F]FEM can quickly cross the blood brain barrier (BBB) and quickly fade out. Abstract: In the 21st century, the incidence and mortality of cancer, one of the most challenging diseases in the world, have rapidly increased. The purpose of this study was to develop 2-(2-[ 18 F]fluoroethoxy)ethyl 4-methylbenzenesulfonate ([ 18 F]FEM) as a positron emission tomography (PET) agent for tumor imaging. In this study, [ 18 F]FEM was synthesized with a good radiochemical yield (45.4 ± 5.8%), high specific radioactivity (over 25 GBq/μmol), and commendable radiochemical purity (over 99%). The octanol/water partition coefficient of [ 18 F]FEM was 1.44 ± 0.04. The probe demonstrated good stability in vitro (phosphate-buffered saline (PBS) and mouse serum (MS)), and binding specificity to five different tumor cell lines (A549, PC-3, HCC827, U87, and MDA-MB-231). PET imaging of tumor-bearing mice showed that [ 18 F]FEM specifically accumulated at the tumor site of the five different tumor cell lines. The average tumor-to-muscle (T/M) ratio was over 2, and the maximum T/M values reached about 3.5. The biodistribution and dynamic PET imaging showed that most probes were metabolized by the liver, whereas a small part was metabolized by the kidney. Moreover, dynamic brain images and quantitative data showed [ 18 F]FEM can quickly cross the blood brain barrier (BBB) and quickly fade out, thereby suggesting it may be a promising candidate probe for the imaging of brain tumors. The presented results demonstrated that [ 18 F]FEM is a promising probe for tumor PET imaging.